Baseline CSF ferritin levels were associated with trajectories of depressive symptoms among older people without dementia - Wang, Qing; Ye, Xinwu; Lin, Yongjian (Frontiers in Aging Neuroscience, 2025)
BackgroundPrevious studies have suggested a link between ferritin levels in the blood and depressive symptoms. However, no prior studies have investigated the association between cerebrospinal fluid (CSF) total ferritin, ferritin light chain, and ferritin heavy chain and longitudinal changes in depressive symptoms among older people without dementia.MethodsIn this study, 543 older people without dementia were included, comprising 163 cognitively unimpaired (CU) participants and 380 participants with mild cognitive impairment (MCI). A non-parametric k-means longitudinal cluster analysis was performed to identify distinct trajectories of depressive symptoms, which were measured using the 15-item Geriatric Depression Scale (GDS-15) over a period of 5 years. Multinomial logistic regression models were used to examine the relationship between CSF total ferritin, ferritin light chain, and ferritin heavy chain levels and the trajectories of depressive symptoms, adjusting for potential covariates.ResultsWe identified three distinct trajectories of depressive symptoms: consistently low (trajectory 1, n = 364; mean age: 73 ± 7 years; percentage of females: 43%), moderately increasing (trajectory 2, n = 149; mean age: 72 ± 7 years; percentage of females: 43%), and rapidly increasing (trajectory 3, n = 30; mean age: 72 ± 8 years; percentage of females: 47%). Compared with trajectory 1, there was a significant relationship between membership in trajectory 3 and CSF total ferritin levels (OR = 0.04, 95% CI = 0.01 to 0.18, p < 0.001). Similarly, CSF ferritin light chain and heavy chain levels showed a similar pattern to that of CSF ferritin levels.ConclusionOur study identified three distinct trajectories of depressive symptoms in older adults without dementia. We observed that lower CSF ferritin levels were associated with a higher likelihood of membership in the rapidly increasing symptom trajectory.